Heterogeneous metal-based catalysts for cyclohexane synthesis from hydrodeoxygenation of lignin-derived phenolics. (15th July 2023) - Lang, Man; Li, Hao
Graphic abstract: Highlights: Hydrodeoxygenation is a versatile strategy to produce jet fuel range hydrocarbons from biomass. Different catalytic systems for the HDO of lignin-derived phenolics to cyclohexane are discussed. Advancements in efficient catalysts towards the synthesis of renewable cyclohexane are displayed. Catalytic HDO reaction mechanism of phenolics involving highly effective catalysts is elaborated in detail. Provision of the perspectives and opportunities for future research in this field. Abstract: The over-reliance on the fossil energy requires the exploitation of sustainable biomass feedstock for supporting the fuel and chemical supply in modern society. Cyclohexane is an exceedingly important precursor for the manufacture of polymers, chemicals and biofuels. In view of the growing demand for cyclohexane and the unsustainability of traditional petroleum-based production processes, continuous effort has been invested in the synthesis of cyclohexane from greener and abundant biomass resources. This review systematacially pays attention to the recent achievements in catalysts for the hydrodeoxygenation conversion of lignin-derived phenolics into cyclohexane. In the meantime, the characteristics of novel catalysts and reaction mechanisms involved also are further summarized and discussed with the purpose of providing a perspective for the design and development of the highly active catalysts. Finally, some personal suggestions for improving the existing challenges and potential opportunities within this promising field are displayed in order to inspire widespread scientists committed to a low-carbon society to make biomass resources play a key role in fuel and chemical production.